Lung cancer biopsy: Can diagnosis be changed after immunohistochemistry when the H&E-Based morphology corresponds to a specific tumor subtype? - Fabiola Del Carlo Bernardi; Marcela Del Carlo Bernardi; Teresa Takagaki; Sheila Aparecida Coelho Siqueira; Marisa Dolhnikoff (Clinics, 2018)
OBJECTIVES: Advancements in non-small cell lung cancer treatment based on targeted therapies have made the differentiation between adenocarcinoma and squamous cell carcinoma increasingly important. Pathologists are challenged to make the correct diagnosis in small specimens. We studied the accuracy of an immunohistochemical panel in subclassifying non-small cell lung cancer in routine small biopsies and compared the results with the diagnosis from resected lung specimens, autopsy samples or biopsied/resected metastases. METHODS: In total, 340 lung cancer biopsies were investigated for the expression of CK5, TTF1, p63 and surfactant. RESULTS: We characterized 166 adenocarcinomas and 124 squamous cell carcinomas. Overall, 85% of cases displayed binary staining (TTF1 positive/p63 negative, and vice versa). The diagnoses of ten cases with a morphology that indicated a specific tumor subtype were changed after immunohistochemistry (IHC). A second specimen was available for 71 patients, and the first diagnosis at biopsy was confirmed in 95% of these cases. Most non-small cell lung cancer cases present a binary immunohistochemical profile in small biopsies, contributing to good diagnostic accuracy with routine markers. In a small proportion of cases, the diagnosis can be changed after IHC even when the morphological aspects indicate one specific tumor subtype. CONCLUSIONS: We recommend that routine small biopsies of lung cancer without classic morphology should be subjected to a minimum immunohistochemical panel to differentiate adenocarcinoma from squamous cell carcinoma.